Analisis Pergeseran Perilaku Konsumen Dalam Niat Beli Di Sektor Otomotif E-Commerce Indonesia - Andres Dharma Nurhalim (Jurnal Bina Manajemen, 2021)
The growth of active internet users in Indonesia is increasing positively. Smartphone users in Indonesia are projected to be the largest in the world wide. This traction creates opportunity for the presence of e-commerce. Nowadays, e-commerce is not only selling a low involvement product but also selling high involvement product in this study a new car. This study aims to analyze the relationship between social commerce construct to trust and purchase intention, consumer trust to purchase intention and perceived risks, perceived risk to purchase intention and perceived benefit to purchase intention. This study used questionnaire as tools to gather data from 200 respondents who never bought a new car through e-commerce. Partial least squares structure equation modelling (PLS-SEM) is used in this study to analyze the data. The result of this study showed that social commerce construct has influence on trust and purchase intention, other variable such as perceived risk also has influence on purchase intention